Risk of a post-colonoscopy colorectal cancer in patients with diverticular disease: a population-based cohort study - Troelsen, Frederikke S.; Sørensen, Henrik T.; Erichsen, Rune (Endoscopy, 2024)
Background Post-colonoscopy colorectal cancers (PCCRCs) may account for up to 30% of all colorectal cancers (CRCs) diagnosed in patients with diverticular disease; however, absolute and relative risks of PCCRC among these patients undergoing colonoscopy remain unknown.Methods We performed a cohort study (1995–2015) including patients with and without diverticular disease who underwent colonoscopy. We calculated 7–36-month cumulative incidence proportions (CIPs) of PCCRC. We used Cox proportional hazards regression models to compute hazard ratios (HRs) of PCCRC, comparing patients with and without diverticular disease, as a measure of relative risk. We calculated 3-year PCCRC rates, as per World Endoscopy Organization recommendations, to estimate the proportion of CRC patients with and without diverticular disease who were considered to have PCCRC. We stratified all analyses by PCCRC location.Results We observed 373 PCCRCs among 56 642 patients with diverticular disease and 1536 PCCRCs among 306 800 patients without diverticular disease. The PCCRC CIP after first-time colonoscopy was 0.45% (95%CI 0.40%–0.51%) for patients with and 0.36% (95%CI 0.34%–0.38%) for patients without diverticular disease. Comparing patients with and without diverticular disease undergoing first-time colonoscopy, the adjusted HR was 0.84 (95%CI 0.73–0.97) for PCCRC and 1.23 (95%CI 1.01–1.50) for proximal PCCRCs. The 3-year PCCRC rate was 19.0% (22.3% for proximal PCCRCs) for patients with and 6.5% for patients without diverticular disease.Conclusions Although the absolute risk was low, the relative risk of proximal PCCRCs may be elevated in patients with diverticular disease undergoing colonoscopy compared with patients without the disease.